2021
DOI: 10.1039/d0cc07502g
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalyst and additive-free visible light induced trifluoromethylation–arylation ofN-arylacrylamides with Umemoto's reagent

Abstract: A visible light induced highly convenient and practical method for the trifluoromethyl–arylation of N-arylmethacrylamides has been developed using Umemoto*s reagent as the trifluoromethyl source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…The reaction is proposed to proceed through an ortho ‐quinone methide before a terminal malonitrile‐mediated [4+2] cyclization step to form the trifluoromethylated product. Huang, Zhang, and coworkers showed the synthesis of trifluoromethylated 2‐oxindoles utilizing 23 under metal‐free blue light irradiation [159] …”
Section: Trifluoromethylation (Cf3)mentioning
confidence: 99%
“…The reaction is proposed to proceed through an ortho ‐quinone methide before a terminal malonitrile‐mediated [4+2] cyclization step to form the trifluoromethylated product. Huang, Zhang, and coworkers showed the synthesis of trifluoromethylated 2‐oxindoles utilizing 23 under metal‐free blue light irradiation [159] …”
Section: Trifluoromethylation (Cf3)mentioning
confidence: 99%
“…[61] An analogous method was also reported, which utilized cheap TfCl. [62] In 2018, Cai and coworkers reported that irradiation of CF 3 SO 2 Na with blue LEDs in the presence of an organic photocatalyst and some oxygen (which served as final electron acceptor) is also efficient for this transformation. [63] Finally, Huang, Zhang, and coworkers have recently reported a very mild and simple photochemical method, which did not require any photocatalyst or additive (Scheme 18).…”
Section: Scheme 11 Photochemical Trifluoromethylative Transformation ...mentioning
confidence: 99%
“…CF 3 radical precursor under mild reaction conditions (Scheme 30). [50] The strategy neither required a photocatalyst nor a base and afforded the target products in moderate to good yields. The N ‐arylacrylamides with electron‐withdrawing and electron‐donating groups performed efficiently, delivering the target products in excellent yields.…”
Section: Cyclization Approachmentioning
confidence: 99%